AKTIVITAS SISWA DALAM PEMBELAJARAN DENGAN MENGGUNAKAN MEDIA FLASHCARD DI SEKOLAH DASAR - KUKUH FEBRIANTO; VIA YUSTITIA; APRI IRIANTO (Universitas PGRI Adi Buana, 2020)
The purpose of this study was to determine the activity of class III-A students in learning using flashcard media at Tenggilis Mejoyo 1 Elementary School Surabaya. This research is a descriptive qualitative research. The subject of this study was class III-A students at Tenggilis Mejoyo 1 Elementary School Surabaya Academic Year 2018-2019 which consisted of 29 students. Data collection techniques include observation, interviews, and documentation. Data analysis using data collection, data reduction, data presentation, conclusion drawing. The validity of the data uses Triangulation techniques. The results showed that the activity of class III-A students in learning using flashcard media in Tenggilis Mejoyo 1 Elementary School Surabaya was said to be good, this was seen through visual activity activities in the form of students observing when learning took place, oral activity in the form of students daring to express opinions, writing activity namely by recording from what is heard and seen, listening activity which is listening to the learning delivered.